Penerapan Model Role Playing Terhadap Keterampilan Komunikasi Verbal Bahasa Indonesia Siswa Kelas V SD Muhammadiyah 5 - Mardan, Zenif Hirga (Gunahumas, 2022)
The low verbal communication of students has an effect on student achievement. Therefore, efforts are needed to improve students' verbal communication skills, one of which is by using the Role Playing learning model. The purpose of this study was to determine the effect of implementing the Role Playing learning model on students' Indonesian verbal communication skills. The population in this study were fifth grade students of SD Muhammadiyah 5. The sample was selected based on the saturated sampling technique, namely the sampling technique when members of the population were used as samples. The class that was selected as the experimental class that applied the role playing learning model was class V SD Muhammadiyah 5 with a total of 29 students. From the data analysis of the pretest (pretest) and the final test (posttest), it is known that the results of the posttest of verbal communication skills are better than the results of the pretest. This can be seen from the average score of the students' pretest, which is 51.1, while the average score of the students' posttest is 76.3.Keywords: Verbal Communication; Indonesian Language; and Role Playing Learning Model.